HEAVY METALS CONTENT OF COPPER (CU) AND LEAD (PB) IN CODIUM FRAGILE SEAWEED - Hidayatullah, Nasrul; Yasir, Inayah; Tahir, Akbar (Jurnal Ilmu Kelautan SPERMONDE, 2023)
This study aims to determine the concentration of copper (Cu) and lead (Pb) inseaweed Codium fragile and is expected to add information about copper (Cu) and lead (Pb) which accumulates inseaweed C. fragile in Puntondo waters. , Takalar Regency. This research was conducted from January to August 2021, located in Puntondo waters, Takalar Regency. This research method collects data in the form of seaweed samples from the field and seaweed obtained from seaweed sales. Data analysis was carried out using the One Way Anova test with a further test of LSD (Least Significant Difference). The results of this study indicate that the metal content of copper (Cu) at each research station in seawater and C. fragile samples has passed the threshold, while the content of lead (Pb) at each station in seawater and C. fragile samples has not passed the threshold based on PP No. 22 of 2021 (<0.008 mg/L) for sea water and BPOM Regulation No. 23 of 2017 (<0.2 mg/kg) for consumption materials. The metal content of copper (Cu) in seawater at each research station was significantly different and the metal content of copper (Cu) in C. fragile at each research station was not significantly different. The metal content of lead (Pb) in C. fragile seaweed at each research station was significantly different and the metal content of lead (Pb) in seawater at each station was below the detection limit of the instrument (<0.01 ppm). The highest content of copper (Cu) in seawater was found at stations near from the ships activity, that is 0.3625 mg/L, followed by stations close to settlements at 0.235 mg/L. The highest content of copper (Cu) in C. fragile was found at stations close to settlements at 6.63 mg/kg followed by stations at PPI Beba at 6.1575 mg/kg and stations close to ships activity at 4,965. mg/kg.